PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI PADA SISWA SMA NEGERI 1 PALU - Ibrahim, Anna Sylvia. E. (Katalogis, 2017)
This research aimed to analyze the impact of PBL model towards the learning result of economics at the students of SMA Negeri 1 Palu. This experimental research used a Randomized Pre Test-Posttest Control Design. The subject or population of this research was the students at class XI IPS SMA Negeri 1 Palu. The selected samples were Class XI IPS 5 as the experimental class and Class XI IPS 3 as the controlled class. The technique for selecting the first phase sample was done by using purposive samplingÂ  and the second phase by using random sampling. The independent variable of this research was problem based learning model and the dependent variable was the score fo learning result of economics of the students at SMA Negeri 1 Palu. Data collecting was done through learning result test. Instrument validation was done by calculating the item discrimation and difficulty index, whereas reliability was calculated by using KR-20. Test data analysis requirements included normality testing by using Kolmogorov-Smirnov and homogenity test by using Levene Test. The hypothesis testing was done by using t test on the significance level of 0,05. Based on the statistic testing result of t test, it was found that the score of F count was 1,585 with the score of p 0,000 was smaller than alpha 0,05 which means that zero hypothesis was rejected. The rejection of zero hypothesis means accepting the alternative hypothesis which stated that there was a difference in learning result between the group of students who were taught by using PBL model in the experimental class compared to the group of students taught by using conventional model in the controlled class. PBL and conventional models were significantly different in the achievement of economics learning result. The difference was strengthen by the mean result of each group. The learning in the experimental class by using PBL model had the mean score of 79.10 while the mean for controlled class using conventional model was 58.93. Based on the finding, it can be concluded that there was an impact on the use of PBL and conventional models towards the learning result of sconomics at SMA Negeri 1 Palu. PBL model gave significant impact towards the learning result of economics at SMA Negeri 1 Palu.